Connection between Pancasila values and Madura Etiquette - Harimurti, Yudi Widagdo; Widodo, Ibnu Sam; Fausta, Moza (Pancasila International Journal of Applied Social Science, 2024)
Self-values/personal values are very important for every person, considering that self-values are life principles, namely values that serve as a guide for a person in making decisions for life and life (self and those around you). In the context of being a state in Indonesia based on the Pancasila philosophy, the life principles of every citizen must reflect the moral values of Pancasila, as referred to in the first to fifth principles. So far, the self-values that Indonesian people carry out in their daily lives follow things taught from generation to generation according to local wisdom. Currently, the world is increasingly global and almost remote, with technology in various fields (especially information) becoming increasingly sophisticated, many things a person does can be known to the public in matter of seconds. People really depend on global information provided by ‘search engines’ such as Google, rather than other information manually because it is considered faster and more accurate, including people looking for clues about self-worth/personal values from various teachings. This greatly influences a person’s actions/decisions/attitudes towards life and life, thereby encouraging self-worth to become an object of research. This research uses a qualitative method with analysis techniques based on a literature review through primary data regarding existing policies in the region and secondary data that is avaliable in various literature, books, journals and website searches. This research also uses a humanist-pluralist perspective, social and sosial theories to explain the framework of the Pancasila self-value guide concept based on Madurese cultural etiquette in collaboration with Brawijaya University (UB). UB was chosen as a research partner considering that Malang is an educational city whose students are very ethnically diverse, so it is hoped that the can provide input and share new strategies for creating locality-based Pancasila self-values. The results of this research are in the form of models and academic texts for draft regional regulations that regulate the community’s obligations to implement local cultural etiquette. It is hoped that this regional policy can preserve Madurese cultural values which can be elevated to self-values as part of the Pancasila principles, apart from that is also provides a solid foundation for building a civilized national character. In this way, it is hoped that Madurese cultural customs will continue to be preserved from generation to generation, which can also elevate Madura as a trigger for the creation of locality-based Pancasila self-values throughout Indonesia.